Flagellin based biomimetic coatings: From cell-repellent surfaces to highly adhesive coatings. (15th September 2016) - Kovacs, Boglarka; Patko, Daniel; Szekacs, Inna; Orgovan, Norbert; Kurunczi, Sandor; Sulyok, Attila; Khanh, Nguyen Quoc; Toth, Balazs; Vonderviszt, Ferenc; Horvath, Robert
Graphical abstract: Abstract: Biomimetic coatings with cell-adhesion-regulating functionalities are intensively researched today. For example, cell-based biosensing for drug development, biomedical implants, and tissue engineering require that the surface adhesion of living cells is well controlled. Recently, we have shown that the bacterial flagellar protein, flagellin, adsorbs through its terminal segments to hydrophobic surfaces, forming an oriented monolayer and exposing its variable D3 domain to the solution. Here, we hypothesized that this nanostructured layer is highly cell-repellent since it mimics the surface of the flagellar filaments. Moreover, we proposed flagellin as a carrier molecule to display the cell-adhesive RGD (Arg-Gly-Asp) peptide sequence and induce cell adhesion on the coated surface. The D3 domain of flagellin was replaced with one or more RGD motifs linked by various oligopeptides modulating flexibility and accessibility of the inserted segment. The obtained flagellin variants were applied to create surface coatings inducing cell adhesion and spreading to different levels, while wild-type flagellin was shown to form a surface layer with strong anti-adhesive properties. As reference surfaces synthetic polymers were applied which have anti-adhesive (PLL- g -PEG poly(l -lysine)- graft -poly(ethylene glycol)) or adhesion inducing properties (RGD-functionalized PLL- g -PEG). Quantitative adhesion data was obtained by employing optical biochips and microscopy. Cell-adhesion-regulating coatings can be simply formed on hydrophobic surfaces by using the developed flagellin-based constructs. The developed novel RGD-displaying flagellin variants can be easily obtained by bacterial production and can serve as alternatives to create cell-adhesion-regulating biomimetic coatings. Statement of Significance: In the present work, we show for the first time that - an oriented and dense monolayer of flagellin molecules mimics the surface of the bacterial flagellar filament. Consequently, the fabricated layer is completely cell repellent. - By genetically modifying flagellin, we incorporate cell adhesion regulating functionalities into this anti-adhesive coating. - We can easily tune the adhesion of living cells from completely cell repellent to highly adhesive.